An approach of designing CONWIP loop for assembly system in one-of-a-kind production environment. Issue 7 (2nd July 2016) - Huang, Guodong; Chen, Jie; Wang, Xiuli; Shi, Yiqun
Abstract : Pursuit of the shortest cycle time does not enhance benefits in one-of-a-kind production (OKP) environment. The quality of services is affected by the delivery on time for OKP enterprise, and a well-designed constant work in process (CONWIP) loop structure can effectively improve the performance of assembly system in OKP. The designed CONWIP loop structures have been tested by simulation under 2 assembly proportion conditions and 14 situations of fluctuation combinations, and analysed relationship between cycle time and punishment of tardiness. Simulation test shows that some of CONWIP policies have stronger robustness, which can perform well in several fluctuation situations. The authors propose an idea of dynamic configuration for CONWIP control. Furthermore, the design procedure of CONWIP can provide a reference and guidance for the application of CONWIP. This article extends the knowledge of OKP shop floor control and promotes implementation of CONWIP in pull manufacturing system.